1997
DOI: 10.1111/j.1440-1746.1997.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antioxidants in ulcerative colitis and their relationship to disease severity and activity

Abstract: Oxygen free radicals produced by neutrophils are important in the pathogenesis of mucosal damage in ulcerative colitis. Vitamin A, vitamin E and cysteine in the plasma can scavenge free radicals. In the present study, plasma levels of vitamin A, vitamin E, cysteine, cystine and protein-bound cysteine were measured in active ulcerative colitis before and immediately after treatment of the active disease, and correlated with disease severity, extent and activity. Plasma vitamin A and cysteine were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…The decrease in serum antioxidants of UC patients may be explained by increased consumption of antioxidants by the recently in¯amed tissue rather than by impaired digestion and absorption of nutrients, which is unlikely in UC patients. Studies showed that the antioxidant defence may be depleted by increased reactive oxidative species found in in¯amed mucosa of IBD patients (Simmonds & Rampton, 1993;Gross et al, 1994;Ramakrishna et al, 1997). It is therefore possible that the antioxidant status in UC patients of the present study was not completely restored after the recent in¯ammation period.…”
Section: Discussionmentioning
confidence: 66%
“…The decrease in serum antioxidants of UC patients may be explained by increased consumption of antioxidants by the recently in¯amed tissue rather than by impaired digestion and absorption of nutrients, which is unlikely in UC patients. Studies showed that the antioxidant defence may be depleted by increased reactive oxidative species found in in¯amed mucosa of IBD patients (Simmonds & Rampton, 1993;Gross et al, 1994;Ramakrishna et al, 1997). It is therefore possible that the antioxidant status in UC patients of the present study was not completely restored after the recent in¯ammation period.…”
Section: Discussionmentioning
confidence: 66%
“…We have also shown in a model of TNBS-induced colitis that lipid peroxides are increased significantly in the colonic mucosa [4], and treatment with SOD improves the colitis score [13]. Several studies on human inflammatory bowel disease confirm that oxidative stress is created by overproduction of reactive oxygen species or by the decrease in plasma concentrations of antioxidants, including vitamins C and E [9,[14][15][16]. Aghdassi and Allard [10] recently measured breath pentane output, a marker of lipid peroxidation, in patients with Crohn's disease and found a higher level of breath pentane output when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…Two lines of evidence support our hypothesis: (1) lipid peroxides significantly accumulate in the gastrointestinal mucosa during development of mucosal injury or inflammation, and (2) pretreatment with superoxide dismutase (SOD, a superoxide scavenger) or a hydroxyl radical scavenger greatly attenuates these injuries, as well as inhibiting the increase in lipid peroxides. It has also been proposed that oxygen radical-mediated lipid peroxidation is involved in the development of tissue injury in Crohn's disease and ulcerative colitis [8][9][10], as well as experimental colitis in animal models [4]. Several animal models of human inflammatory bowel disease have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, oxidative stress results from an imbalance between the generation of ROS and endogenous antioxidant systems. ROS are major sources of primary catalysts that initiate oxidation in vivo and in vitro and create oxidative stress which results in numerous diseases and disorders [1] such as cancer [2] , cardiovascular disease [3] , neural disorders [4] , Alzheimer's disease [5] , mild congnitive impairment [6] , Parkinson's disease [7] , alcohol induced liver disease [8] , ulcerative colitis [9] , ageing [10] , and atherosclerosis [11] .…”
Section: Introductionmentioning
confidence: 99%